Contribution of Schema Theory and Social-constructivist Approach to Teaching: the Acquisition Functionalism among Students in Translation Course - Eraković, Borislava R.; Topalov, Jagoda P. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper presents an analysis of how acquired schemas interfere with the development of new schemas in a course on journalistic translation and the role a social-constructivist approach to teaching in fostering the schema change. It is based on the research carried out during 2016/2017 academic year which involved 62 second and third year students of English Language and Literature at the Faculty of Philosophy, University of Novi Sad. The paper begins by relating some aspects of translation competence to the general competences defined within the EU Tuning Project, which are some of the core learning outcomes of any university level education (critical thinking, reading and writing, finding relevant information and application of theoretical knowledge to solve problems). This is followed by an overview of the educational context and key concepts for this level of translator training – understanding the limits of the equivalence theory and the application of the functionalist approach to translation. The core part of the paper presents the results of the research that is based on a linguistic and a translational test, aiming to establish the students’ English language competence level (CEFR) and their dominant schema of translation. The linguistic test has shown that students have attained a C1 or C2 level of language competence. The translational test identified the categories the students employ in the analysis of the relations between the given source and target journalistic text. Both quantitative and qualitative analyses were applied to the resulting data, with the following set of variables in the investigation: independent variables included the CEFR level and the year of study, whereas the dependent variables included the 12 initially identified categories in students’ responses on the translational test. Relationships between the variables were tested by means of chi-square tests and binary correlation tests in statistics software SPSS 20. The results show that (1) the difference in language competence (C1 and C2) is not significantly related to the types of translational categories the students applied in the comparison of the source and the target text, (2) that the year of study is a significant variable for some of the categories of comparison (textual cohesion between the title and the lead, the role of the target reader and level of formality) and (3), that there is a significant correlation between some of the categories students identify when analysing the relations between the source and target text. This last finding confirms the authors’ supposition that the students’ dominant schema of translation is an operation of pairing lower-level linguistic units between the source and target text (equivalence theory), unmitigated by the extratextual factors (functionalism). The understanding of these findings within the framework of schema theory bears considerable pedagogical implications, which are presented in the concluding part of the paper. According to cognitivists, schemas are most effectively changed when the existing knowledge is not enough to understand the real world phenomena, i.e. when a “disequilibrium is created“ between an old schema and new information (Derry 1996, p. 165). As our research has shown, the initial lecture on functionalism and teacher-guided discussion prior to testing achieved little in the way of making them change their dominant schema of what constitutes translation. Social-constructivist approach, which relies on exposing students to real life situations and a classroom scenario based on a collaborative problem solving, is likely to be more effective. This is indicated by the results of translational test which has shown that students examined different aspects of the source and target communicative situation. Collaboration involving argumentation makes students identify their assumptions, and negotiation involves their reconsideration. This type of activity creates a more effective disequilibrium, which, according to schema theory, is crucial element in schema change and the acquisition of new knowledge.